PERANCANGAN SISTEM INFORMASI PEMESANAN PAKET WEDDING DAN PREWEDDING PHOTOGRAPHY PADA STUDIO AAN UNCHU PHOTOGRAPHY BERBASIS WEB - Aditya Franatiaga; Silfia Andini; Harkamsyah Andrianof (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
At Studio Aan Unchu Photography, some activities are still not computerized, as a result, Studio Aan Unchu photography often receives complaints from customers. This can create a negative impression of the services of Studio Aan Unchu Photography, this negative impression will have an impact on decreasing the trust of prospective customers which is caused by negative reviews from previous customers. There are many changes to photo session schedules, especially pre-wedding, which suddenly require customers to rearrange their busy schedules and adjust to the new schedule. The scheduling system mechanism at Studio Aan Unchu Photography is still a mess, resulting in difficulties in allocating teams and the availability of equipment. By using the Information System for Ordering Wedding and Prewedding Photography Packages, it can speed up and make it easier for customers to place orders without having to come directly to the Aan Unchu Photography Studio, can be used as an auxiliary media in increasing the number of sales of wedding and prewedding photography packages, can provide accurate information about prices packages offered and shooting schedules.